A Lexical Profiling Analysis of State Islamic Higher Education Entrance Examinations: Implications for Vocabulary Breadth and Test Accessibility - Dhinuk Puspita Kirana; Aries Fitriani (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Vocabulary knowledge plays a crucial role in reading comprehension and is widely recognised as one of the strongest predictors of successful reading performance among second language learners(Reynolds, 2021); however, the lexical demands of university entrance examinations may not always correspond to the vocabulary knowledge developed through secondary-school English curricula. This issue is particularly relevant in the State Islamic Higher Education Admission Test (UM-PTKIN), whose reading passages frequently incorporate Islamic and culturally specific content. Therefore, this study investigates the lexical profile of the English component of the UM-PTKIN examination and examines its implications for vocabulary breadth and test accessibility. Using a descriptive quantitative design, four English test scripts from the 2019 UM-PTKIN examination were analyzed through lexical profiling with RANGE, FREQUENCY, VocabProfile, and AntConc. The analysis focused on tokens, word types, and word families, with word families adopted as the primary unit because they provide a more realistic estimate of learners’ vocabulary knowledge in educational assessment contexts. The findings revealed that the test relied predominantly on high-frequency vocabulary; however, a substantial proportion of vocabulary items fell outside established frequency lists. Many of these off-list items consisted of Islamic terminology, proper nouns, and culturally embedded expressions rather than advanced English vocabulary. These findings suggest that vocabulary demands in UM-PTKIN are influenced not only by lexical frequency but also by thematic and cultural familiarity. The study provides implications for test development, curriculum alignment, and vocabulary instruction in Islamic higher education contexts.